أثر الأمن الوظيفي على ظاهرة الصمت التنظيمي بالمؤسسات العمومية الجزائرية: دراسة حالة موظفي جامعة خميس مليانة - صادفي، جمال; خثير، محمد (جامعة علي لونيسي البليدة 2 - مخبر تسيير الجماعات المحلية ودورها في تحقيق التنمية, 2021)
يهدف هذا البحث إلى دراسة العلاقة التأثيرية بين الأمن الوظيفي وظاهرة الصمت التنظيمي لدى موظفي جامعة خميس مليانة، بالاعتماد على الاستبيان كأداة لجمع البيانات، وبعد توزيع (180) استمارة استبيان تم استرجاع (116) استمارة صالحة للتحليل، وباستخدام برنامج (SPSS v26)، توصلت الدراسة إلى أن هناك مستوى متوسط من الإحساس الأمن الوظيفي لدى أفراد العينة، وكان مستوى الصمت التنظيمي مرتفعا، كما أكدت النتائج وجود تأثير معن و ي وعكس ي لعامل الأمن الوظيفي في الحد من سلوك الصمت التنظيمي، لذا نوصي بضرورة الأخذ بالاعتبار آراء الموظفين ومعرفة المشاكل التي يعانون منها داخل الجامعة التي تحول دون التمتع بدرجة عالية من الأمن الوظيفي، بالإضافة إلى تشخيص العوامل التي تسبب سلوك الصمت، وذلك من أجل الوصول إلى حلول واقعية للحد مستقبلا من تفشي هذه الظاهرة السلبية التي أصبحت تؤرق التقدم والتطور التنظيمي بالمؤسسات الجامعية الجزائرية، والعمل على تمكين وتشجيع الموظفين ومنحهم الحرية الواسعة للمساهمة في حل مختلف المشاكل التنظيمية.
This research aims to study the impact of the relationship between job security and the phenomenon of organizational silence among the employees of the University of Khemis Miliana, relying on the questionnaire as a tool for data collection, and after distributing (180) questionnaires, (116) valid forms were returned for analysis. , and using the (SPSS v26) program, the study concluded that there is a medium level of security job among the interviewed employees, while the level of organizational silence was high, and the results confirmed the existence of a clear A significant and opposite effect of the job security factor in reducing the behavior of silence Organizational Therefore, we recommend the need to take into account the opinions of the employees and know the problems they suffer within the university that prevent them from enjoying a high degree of job security, which in turn is reflected in the organizational conditions, and to diagnose the factors that cause the behavior of silence, in order to reach realistic solutions to reduce the future spread of this negative phenomenon that has become disturbing the progress and organizational development in Algerian university institutions, and work to empower and encourage employees and give them wide freedom to contribute to solving problem problems.
Keywords: سلوك الصمت -- السلوك التنظيمي -- الراحة النفسية -- الأداء البشري